Die Ambivalenz der Religionen, (Teil 3) - Stümke, Volker (Theologische Rundschau, 2025)
The talk of the ambivalence of religions was brought to a term by R. Scott Appleby's monograph "The Ambivalence of the Sacred. Religion, Violence, and Reconciliation" from the year 2000 (Rowman & Littlefield, NewYork), which is still relevant. On the one hand, religions can have an affinity for violence, on the other hand they can realize peace and reconciliation. But how these profiles relate to each other is still widely disputed. This review presents and an alyses publications on this topic from the period 2019 to 2023. As in the previous review (ThR 84 [2019], 40-95 & 105-157), conceptual investigations are first presented (Chapter 1), followed by an analysis of the relationship between religion and violence (Chapter 2) and then the concrete relationship between Christian faith and military violence (Chapter 3). This is followed by adescription of the aspects of the Christian faith that are both pro-violence and pro‐peace (chapter 4), before finally presenting interreligious studies and projects(chapter 5).